1996
DOI: 10.1080/00039896.1996.9936000
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Chromium, and Cadmium Exposure during Abrasive Blasting

Abstract: An evaluation of lead, cadmium, and chromium exposure was conducted during abrasive blasting of a steel bridge to remove paint in preparation for repainting. Airborne lead concentrations were measured at several locations inside the containment structure, as well as near the workers' breathing zones. Airborne cadmium and chromium were also measured in the containment area. Blood lead levels were monitored in each worker. Airborne lead and cadmium levels in containment exceeded the Occupational Safety and Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
2
17
1
Order By: Relevance
“…A large number of construction workers from varying facets of this industry are exposed to airborne lead during the demolition and renovation of buildings [5]. Numerous reports and case studies have been published on lead abatement practices [3,[12][13][14][15], but little information currently exists on exposure associated with different procedures involved with the demolition or remodelling industries [11]. Most lead exposure studies have focused on steel structure activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of construction workers from varying facets of this industry are exposed to airborne lead during the demolition and renovation of buildings [5]. Numerous reports and case studies have been published on lead abatement practices [3,[12][13][14][15], but little information currently exists on exposure associated with different procedures involved with the demolition or remodelling industries [11]. Most lead exposure studies have focused on steel structure activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most lead exposure studies have focused on steel structure activities (e.g. bridges) [3,12,[15][16][17]18]. Current lead regulations have been designed to protect public health, the environment and those occupationally employed in the lead industry [6,19].…”
Section: Introductionmentioning
confidence: 99%
“…Because most work has focused on Pb, an analysis of Ba concentrations in paint waste has seldom been reported (Conroy et al, 1996;Mielke et al, 2001). Interestingly, concentrations of Pb and Cr in the paint waste samples follow a similar trend.…”
Section: Metal Distribution In the Paint Wastementioning
confidence: 99%
“…Studies of paint particles/associated waste have focused on the distribution of Pb (Bernecki et al, 1995;Beckley and Groenier, 2008;Brumis et al, 2001;Daniels et al, 2001;MnDOT, 2004) with occasional measurements of other metals such as As, Cr, Cd, Hg, and Zn (Conroy et al, 1996;Mielke and Gonzales, 2008;Turner and Sogo, 2012). Mielke and Gonzales (2008) found that Pb concentrations were independent of Hg in interior and exterior paint sampled from New Orleans homes.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of the waste is determined by Toxicity Characteristic Leaching Procedure (TCLP) tests and depending on the characteristics of the waste the spent abrasive must be disposed off as solid or hazardous waste [8,11,12]. Owing to the environmental impacts of the process and waste management challenges faced for safe disposal of the wastes, United States Environmental Protection Agency (US EPA) encourages industries, businesses, and institutions to consider all pollution prevention options to aid environmentally preferable purchasing (EPP).…”
Section: Significance Of Productivity and Consumptionmentioning
confidence: 99%